HUBUNGAN STRATEGI PEMBELAJARAN MANDIRI MELALUI DARING OLEH GURU TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI RUPA DI SMPN 26 PADANG - Mursalina Mursalina; Zubaidah Zubaidah (Serupa The Journal of Art Education, 2020)
This study aims to determine whether there is a significant relationship between online independent learning strategies by teachers and student learning outcomes in fine arts learning at State of Junior High School 26 Padang. This type of research is a quantitative correlation study. The population in this study were all students of class VII in State of Junior High School 26 Padang. Sampling in this study using a proportional random sampling technique (random technique). The results of data  testing show that there is no significant relationship between online independent learning strategies by teachers and student learning outcomes in fine arts learning with a significance value of 0.923> 0.05, this value is much higher than the 0.05 sig level. Thus the conclusion is that online  independent learning strategies do not have a significant relationship with student learning outcomes in fine arts learning at State of Junior High School 26 Padang.Keywords: Learning strategies, Online learning, Learning outcomes Art